Perlindungan Hukum Bagi Kreditor Terhadap Pelunasan Piutang Dari Harta Pailit - Hamdi Hamdi; Sulaiman S; Teuku Yudi Afrizal (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2018)
The concept of legal protection in bankruptcy has so far been seen as a way out of the problem of accounts receivable debt which coincides with a bankrupt debtor, where the debtor no longer has the ability to repay the debts which are past due to their creditors, so that the steps to submit a request for the determination of bankruptcy status by the Court Commerce of the debtor is a possible step to resolve the bankruptcy case. Bankruptcy was originally regulated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK and PKPU). Furthermore, if the parties submitting bankruptcy applications, the Commercial Court Judges at the District Court are required to examine and hear the case being submitted. The research method used is the normative legal research method or library research with the statute aprroach approach and the case aprroach approach. Based on the results of the study, it is known that the form of legal protection for creditors against paying off debts from bankrupt assets in the Supreme Court Decision Number 511 / K / Pdt. Yinchenindo Mining Industry (in bankruptcy) by law becomes a guarantee for its debts to preferred creditors, in this case the Head of the Second Foreign Capital Investment Service Tax Office. Furthermore, the UUK and PKPU also guarantee the rights of creditors in bankruptcy, especially the rights of preferred creditors who have a special position with peace efforts and the postponement of obligations to pay debts of bankrupt debtors to their creditors as stipulated in Article 222 of the UUK and PKPU. The concept of the distribution of bankrupt assets distributed to preferred creditors after deducting bankruptcy fees and compensation for curatorial services where the payment process is settled based on the principle of fairness and balance set forth in Article 265 of the UUK and PKPU, where the preferred creditor parties receive the remaining payment of the receivables amounting to 62.5% ( sixty two point five percent) of the bankruptcy assets.It is expected that the Judges of the Commercial Court and the Court of Appeals at the Supreme Court consider the rights of preferred creditors who pay off their receivables first. The Debtor should be able to immediately submit a request to postpone the debt payment obligation so that the remaining outstanding debt receivables cannot be paid off to the preferred creditors through the sale of free assets. Keywords: Protections of the law, creditor, Treasures of starc